Growth, carcass characteristics, weight of internal organs and meat proximate composition of six genotypes in chickens reared in Andean region of northern Peruvian (Scientia Agropecuaria, 2020)
This study examined the growth, carcass characteristics, weight of internal organs, meat quality and meat proximate composition in six genotypes of chickens reared in Andean region of northern Peruvian, with intensive system, using 600 chickens one-day-old, divided in to six equally sized groups. The comparison included two Creole chicken breeds from Peru, improved and pure, and four imported chicken strains (Hubbard Red, Hubbard White, Native French, and Babcock). The animals were fed without restriction and slaughtered 13 weeks of age. Chickens of the imported strains, especially Hubbard chickens were heavier at slaughter than creoles breeds. Proportions of cuts: thigh, drumstick and head were similar among genotypes, carcass yield, breast meat and abdominal fat were lowest in the Creole breed and Native French. There were no statistical differences (p > 0.05) for meat pH, drip loss, and cooking loss in response to genotype. The breast meat of the two Creole breeds had lower contents of fat compared with that of the Hubbard strains.
Keywords: genotype; creole chicken; growth; carcass; High-Andean region.